Endoscopic Evacuation of Intracerebral Hematoma Utilizing a Side-Cutting Aspiration Device. Issue 6 (12th October 2019) - Shao, Jianning; Witek, Alex; Borghei-Razavi, Hamid; Bain, Mark; Recinos, Pablo F
Abstract: BACKGROUND: Intracerebral hemorrhage (ICH) is associated with a significant mortality of up to 50%, with almost all survivors suffering from debilitating functional compromise. In most cases, open craniotomy has failed to yield significant survival benefit. However, emerging evidence suggests that minimally invasive surgery (MIS) may yield clinically significant improvements in patient survival and quality of life in cases where open craniotomy has not shown benefit. CASE PRESENTATION: We report the first documented usage of a side-cutting-aspiration device via an endoscopic approach for the evacuation of a 56cc hematoma, which was a technical modification on previous MIS techniques. The patient is a 50-yr-old female who was transferred emergently to our center with a National Institutes of Health Stroke Scale score of 27 and found to have a large hematoma involving her left basal ganglia. A minimally-invasive approach was elected due to evidence on the risks and suboptimal outcomes of open craniotomy in ICH evacuation. Neuronavigation was used to plan the surgical trajectory for ICH access. Evacuation took place in three main steps: 1) beginning at the center of the clot to remove bulk; 2) mobilizing clots from parenchymal walls to a safe zone via aspiration, followed by clot homogenization; and 3) re-expansion of the cavity via continuous irrigation to allow visualization of further clots. A final inspection was performed to ensure removal of all clots that could be safely removed. The dual functionalities of the device, namely, suction only and suction plus side-cutting functions, enabled key maneuvers, such as clot homogenization and controlled aspiration strength, to be safely performed. A near-total evacuation of the hematoma was achieved without damage to surrounding parenchyma. The patient experienced a rapid clinical course from comatose to discharge-ready in 5 d. At 30-d follow-up, the patient had residual expressive aphasia and was able to ambulate with the assistance of a quad cane. There are no radiographical signs of recurrent hemorrhage or parenchymal injury. Clinical follow-up with this patient is ongoing. CONCLUSION: This is the first ICH evacuation with a side-cutting-aspiration device via an endoscopic approach. In our patient, this technique proved to be safe and efficacious, suggesting that this technique may be a promising addition to the armamentarium of MIS for ICH evacuation.